Poetry of revolution : the poetic representation of political conflict and transition in Milton’s Paradise Lost and Marvell’s Cromwell Poems - Le Roux, Selene (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (English Literature))--University of Stellenbosch, 2007.